TEAD–YAP Interaction Inhibitors and MDM2 Binders from DNA‐Encoded Indole‐Focused Ugi Peptidomimetics - Kunig, Verena B. K.; Potowski, Marco; Akbarzadeh, Mohammad; Klika Škopić, Mateja; Santos Smith, Denise; Arendt, Lukas; Dormuth, Ina; Adihou, Hélène; Andlovic, Blaž; Karatas, Hacer; Shaabani, Shabnam; Zarganes‐Tzitzikas, Tryfon; et al. (Angewandte Chemie International Edition, 2020)
DNA‐encoded combinatorial synthesis provides efficient and dense coverage of chemical space around privileged molecular structures. The indole side chain of tryptophan plays a prominent role in key, or “hot spot”, regions of protein–protein interactions. A DNA‐encoded combinatorial peptoid library was designed based on the Ugi four‐component reaction by employing tryptophan‐mimetic indole side chains to probe the surface of target proteins. Several peptoids were synthesized on a chemically stable hexathymidine adapter oligonucleotide “hexT”, encoded by DNA sequences, and substituted by azide‐alkyne cycloaddition to yield a library of 8112 molecules. Selection experiments for the tumor‐relevant proteins MDM2 and TEAD4 yielded MDM2 binders and a novel class of TEAD‐YAP interaction inhibitors that perturbed the expression of a gene under the control of these Hippo pathway effectors. A focused approach: A DNA‐encoded peptoid library was designed by the Ugi multicomponent reaction around indole structures that mimic the side chain of tryptophan. Applying this focused library to the challenging cancer targets MDM2 and hTEAD4 yielded compounds for inhibitor development. Compounds binding to hTEAD4 disrupted the hTEAD4–YAP interaction, and reduced expression of a gene under control of the TEAD–YAP transcription factor complex.